Cut Detection in Remote Versatile Wireless Sensor Mobile Networks - LEELADHAR annepu (Institute of Advanced Engineering and Science, 2014)
A remote sensor system can get differentiated into different joined segments because of the disappointment of some of its hubs, which is known as a